2017
DOI: 10.1002/pmic.201700161
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to BMAA mirrors molecular processes linked to neurodegenerative disease

Abstract: The goal of this study is to investigate the molecular pathways perturbed by in-vitro exposure of beta-methylamino-L-alanine (BMAA) to NSC-34 cells via contemporary proteomics. Our analysis of differentially regulated proteins reveals significant enrichment (p<0.01) of pathways related to ER stress, protein ubiquitination, the unfolded protein response, and mitochondrial dysfunction. Upstream regulator analysis indicates that exposure to BMAA induces activation of transcription factors (X-box binding protein 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 62 publications
1
32
0
1
Order By: Relevance
“…Although the molecular mechanisms are still to be explored, Staphylococcus aureus α-toxin and Helicobacter pylori vacuolating cytotoxin (VacA) can promote cytotoxicity through mitochondrial impairment (Arnoult et al, 2009). It should be noted here that BMAA may also have the ability to induce mitochondrial dysfunction (Beri et al, 2017). In vitro studies with NSC-34 cells, a cell line of motor neurons showed that BMAA elicited a pronounced decrease in oxidative phosphorylation, altered calcium homeostasis and exacerbated ROS production.…”
Section: Mitochondrial-driven Innate Immunity Activation: a Possible mentioning
confidence: 86%
See 1 more Smart Citation
“…Although the molecular mechanisms are still to be explored, Staphylococcus aureus α-toxin and Helicobacter pylori vacuolating cytotoxin (VacA) can promote cytotoxicity through mitochondrial impairment (Arnoult et al, 2009). It should be noted here that BMAA may also have the ability to induce mitochondrial dysfunction (Beri et al, 2017). In vitro studies with NSC-34 cells, a cell line of motor neurons showed that BMAA elicited a pronounced decrease in oxidative phosphorylation, altered calcium homeostasis and exacerbated ROS production.…”
Section: Mitochondrial-driven Innate Immunity Activation: a Possible mentioning
confidence: 86%
“…While the observation that BMAA interacts very strongly with proteins causing their misfolding has not been disputed, some groups have failed to detect incorporation of BMAA into the primary structure of proteins thus calling into question the role of the misincorporation hypothesis in explaining BMAA's observed neurotoxic effects (Beri et al, 2017;Onselen et al, 2017). Subsequently, alternative mechanisms have been investigated and BMAA has been found to strongly associate with melanin, to selectively inhibit the activity of certain enzymes and to interfere with and disrupt protein refolding in vitro by associating with proteins through electrostatic interactions strong enough to resist TCA precipitation and subsequent washing with SDS or DTT (van Onselen and Downing, 2018).…”
Section: Amino Acid Misincorporation Protein Folding and Neurodegenementioning
confidence: 99%
“…), 21 and that this substitution could promote misfolding and aggregation; 22 it is important to note that other studies have disputed this theory and were not able to detect similar changes. 23 Still other studies have indicated that BMAA indeed interacts with proteins, but instead through a non-covalent association rather than translational misincorporation. 24 These interactions could lead to BMAA influencing other biochemical pathways including ER stress, protein ubiquitination, the unfolded protein response, and mitochondrial dysfunction.…”
Section: Despite the Correlation Between Bmaa And Development Of Neurmentioning
confidence: 98%
“…These results were confirmed by another proteomic study in NSC-34 cells exposed for 72 h to BMAA (500 µM). Indeed, exposure to BMAA resulted in modification of several molecular pathways known to be implicated in ALS pathogenesis, such as ER stress, eIF2 signalling, protein ubiquitination and misfolded protein response pathways [ 58 ]. Interestingly, the expression of various mitochondrial proteins involved in oxidative phosphorylation, TCA cycle and oxidative stress response was found to be perturbed: BMAA favours activation of transcription factors known to regulate oxidative stress and cellular senescence [ 58 ].…”
Section: Protein Incorporation Of Bmaa and Cellular Stressmentioning
confidence: 99%
“…Indeed, exposure to BMAA resulted in modification of several molecular pathways known to be implicated in ALS pathogenesis, such as ER stress, eIF2 signalling, protein ubiquitination and misfolded protein response pathways [ 58 ]. Interestingly, the expression of various mitochondrial proteins involved in oxidative phosphorylation, TCA cycle and oxidative stress response was found to be perturbed: BMAA favours activation of transcription factors known to regulate oxidative stress and cellular senescence [ 58 ]. Whereas these authors aimed to investigate the hypothesis that BMAA could be misincorporated into cellular protein in place of l -Serine, no evidence of BMAA misincorporation in intracellular or secreted proteins was found.…”
Section: Protein Incorporation Of Bmaa and Cellular Stressmentioning
confidence: 99%